The new encyclopedia britannica in 30 volumes. Macropedia VOL.18 / William Benton - Benton, William (1977)
The evolution of teacher education, issues and problems in teacher education, the status of teachers, functions and roles of teachers, the career of the teacher, the teaching profession and contemporary social revolutions, the changing view of technology, a world view of technology s promise and threat, the urran revolution, technological achievements of Greece and Rome, medieval advance, the emergence of western technology, power technology, development of industries, technology.